High S100A8 and S100A12 protein expression is a favorable prognostic factor for survival of oropharyngeal squamous cell carcinoma. Issue 9 (24th October 2014) - Funk, Sonja; Mark, Regina; Bayo, Pilar; Flechtenmacher, Christa; Grabe, Niels; Angel, Peter; Plinkert, Peter K.; Hess, Jochen
<x xml:space="preserve">Abstract</x> S100/calgranulins (S100A8, S100A9 and S100A12) are key players of innate immune function and elevated levels are a characteristic feature of acute and chronic inflammation, and inflammation‐associated carcinogenesis. However, reduced S100A8 and S100A9 expression has been detected for squamous cell carcinoma, including the head and neck region (HNSCC), which originate from mucosal epithelia with abundant expression of both proteins under physiological conditions. In contrast to S100A8 and S100A9, only sparse information is available for S100A12 and a comparative study of all three S100/calgranulins in HNSCC is still missing. We analyzed S100/calgranulin protein levels in a retrospective patient cohort (n = 131) of oropharyngeal squamous cell carcinoma (OPSCC) by immunohistochemical staining of tissue microarrays. Common characteristics of all three S100/calgranulins were: (i) abundant expression in supra‐basal keratinocytes of normal mucosa with predominant nuclear staining, (ii) low expression in 30.4–51.9% of primary OPSCCs and (iii) variable accumulation of S100/calgranulin‐positive immune cells in the tumor stroma. These features were associated with histopathological characteristics, such as tumor grade, lymph node metastasis and tumor stage. Furthermore, univariate and multivariate analysis revealed worse overall survival of OPSCC patients with simultaneous reduction of S100A8 and S100A12 expression, while expression of S100A9 or presence of the S100A8/S100A9 heterodimer had no impact, suggesting distinct regulation and function of individual S100/calgranulins in the pathogenesis of HNSCCs.